Nuclear uptake of 1,25-dihydroxy[3H]cholecalciferol in dispersed fibroblasts cultured from normal human skin. - Eil, C (1981)
Because of the relative inaccessibility of known calciferol target tissues (i.e., intestine and bone), we examined fibroblasts derived from normal human skin and grown in tissue culture as a means of evaluating the interaction of 1,25-dihydroxycholecalciferol [1,25(OH)2D3] and its effector system. When dispersed, intact cells were used, nuclear uptake of 1,25-dihydroxy[23,24(n)3-H]cholecalciferol [1,25(OH)2[3H]D3) was temperature-dependent, optimal at 45 min at 37 degrees C, and saturable. In competition experiments with other calciferols, the 1,25(OH)2[3H]D3 uptake showed specificity indistinguishable from that reported for 1,25(OH)2D3 receptors from calciferol target tissues. Analysis of 1,25(OH)2[3H]D3 nuclear uptake in fibroblast strains from six normal adults (four male, two female) yielded an average binding capacity (R0) of 10,600 +/- 2,000 (SEM) nuclear sites per cell and an apparent dissociation contant (Kd) of 0.50 +/- 0.07 (SEM) x 10(-9) M. Donor sex, donor age, or anatomic site of origin of the cell line did not affect the characteristics of uptake. Similar nuclear uptake was demonstrable with cultured MCF-7 cells (derived from human breast cancer) when assayed in the same fashion. When hypertonic extracts of nuclei obtained from skin fibroblasts incubated with 1,25(OH)2[3H]D3 were subjected to centrifugation on sucrose gradients, a single peak of radioactivity sedimented at approximately 3 S; when excess 1,25(OH)2D3 was coincubated during the cellular uptake phase, this 3S peak was not observed. Molybdate was an essential buffer component for receptor stabilization during cell fractionation and sedimentation analysis. In summary, by using fibroblasts cultured from normal human skin, we have identified a process of nuclear uptake of 1,25(OH)2[3H]D3 with the affinity, saturability, and specificity characteristics of a steroid hormone--receptor interaction. This method should be useful in studying 1,25(OH)2D3 recept physiology in cells from normal persons as well as in cells from patients who have disorders in the responsiveness of calciferol target tissues.